2013
DOI: 10.1063/1.4794066
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced light extraction from InGaN/GaN quantum wells with silver gratings

Abstract: Effect of the band structure of InGaN/GaN quantum well on the surface plasmon enhanced light-emitting diodes J. Appl. Phys. 116, 013101 (2014); 10.1063/1.4886223Effect of plasmonic losses on light emission enhancement in quantum-wells coupled to metallic gratings

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 20 publications
2
33
0
Order By: Relevance
“…Okamoto et al (2004) reported for the first time large photoluminescence (PL) increases from InGaN/GaN QW material coated with metal layers. Homeyer et al (2013) demonstrate that an extraction enhancement by a factor of 2.8 can be obtained for a GaN quantum well structure using metallic nanostructures, compared to a flat semiconductor. Many theoretical and experimental researches have demonstrated that, for the dielectricbased photonics, large portion of electromagnetic waves spread over the space and cannot be confined in a small region due to the diffraction limit of light.…”
Section: Introductionmentioning
confidence: 95%
“…Okamoto et al (2004) reported for the first time large photoluminescence (PL) increases from InGaN/GaN QW material coated with metal layers. Homeyer et al (2013) demonstrate that an extraction enhancement by a factor of 2.8 can be obtained for a GaN quantum well structure using metallic nanostructures, compared to a flat semiconductor. Many theoretical and experimental researches have demonstrated that, for the dielectricbased photonics, large portion of electromagnetic waves spread over the space and cannot be confined in a small region due to the diffraction limit of light.…”
Section: Introductionmentioning
confidence: 95%
“…In this paper, we study using fluctuational electrodynamics a technologically simple extraction enhancement technique introduced in [1], where a metallic nano-grating is deposited on top of the GaN structure and covered with an organic (polymer) layer. Measurements made recently on luminescence enhancement using optical excitation demonstrated that an extraction enhancement factor of up to 2.8 can be obtained from the polymer structure [1], compared to a flat semiconductor structure.…”
Section: Introductionmentioning
confidence: 99%
“…E MISSION enhancement engineering by tailoring the scattering and the optical local density of states (LDOS) of light-emitting diodes (LEDs) is expected to contribute potentially to more efficient energy technologies [1][3]. In particular, indium gallium nitride (InGaN) emitters play a key role in energy-efficient lighting and display components.…”
Section: Introductionmentioning
confidence: 99%
“…This problem seriously hindered the realization of high external quantum efficiency (EQE) of LEDs. Some methods toward improving the LEE of LED devices have been proposed, mainly including photonic crystal (PC) [2,3], localized surface plasmons (LSPs) [4][5][6], patterned substrate [7] and surface roughening [8][9][10][11][12]. Specifically, surface roughening is widely accepted on account of its simple and efficient characteristics.…”
Section: Introductionmentioning
confidence: 99%